TINJAUAN YURIDIS TERHADAP PELAKU DEMONSTRASI YANG MELAKUKAN PERBUATAN MELANGGAR HUKUM BERDASARKAN UNDANG-UNDANG NOMOR 9 TAHUN 1998 TENTANG KEMERDEKAAN MENYAMPAIKAN PENDAPAT DI MUKA UMUM: TINJAUAN YURIDIS TERHADAP PELAKU DEMONSTRASI YANG MELAKUKAN PERBUATAN MELANGGAR HUKUM BERDASARKAN UNDANG-UNDANG NOMOR 9 TAHUN 1998 TENTANG KEMERDEKAAN MENYAMPAIKAN PENDAPAT DI MUKA UMUM - admin, Admin; Irfan Baihaqi; Muhamad Dluha; Rudi Cahyono (JUSTNESS - Jurnal Hukun dan Agama, 2024)
Abstract Expressing opinions in public is a right and can be exercised by anyone because this is protected in the Indonesian constitution. So, as stipulated in the explanation of Law number 9 of 1998 concerning Independence. Expressing opinions in public must be based on the principle of balance between rights and obligations, the principle of deliberation and consensus, the principle of legal certainty and justice, the principle of proportionality, and the principle of benefit. The aim of this research is to determine and analyze law enforcement against demonstration perpetrators who violate the law based on Law Number 9 of 1998 and to determine the supervision of demonstrations so that anarchy does not occur. The benefit of this research is to provide an understanding regarding law enforcement and escorting perpetrators of demonstrations that violate the law. Based on the formulation of the problem and research objectives, the method used is normative juridical, namely by examining statutory regulations, legal theories related to the problem being discussed and based on its nature, using descriptive analytical methods, namely research that describes clearly and carefully the things that are discussed. in question. What is being analyzed is Law Number 9 of 1998 concerning Freedom to Express Opinions in Public. The results of this research illustrate that law enforcement against perpetrators of anarchist demonstrations has been specifically regulated in article 16 of Law Number 9 of 1998 which states that perpetrators or participants in conveying opinions in public who commit acts that violate the law, can be subject to legal sanctions in accordance with the provisions of the Regulations. Applicable legislation. Second, to guard and supervise demonstrations so that anarchy does not occur, procedures for carrying out demonstrations have been established based on Law Number 9 of 1998 which have been regulated in articles 9 to article 14 and have also been regulated in Police Regulation Number 7 of 2012. Keywords: Anarchy, Demonstrations, Unlawful Acts